Peran Guru Bimbingan Konseling dalam Mengatasi Tawuran Pelajar - Setiawan, Eko (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2015)
Brawl among adolescents currently emerging-proliferation. Brawl among students has been as commonplace among students Indonesia. Student brawls itself sometimes based on reasons that are not clear and unreasonable such as among schoolchildren taunted each other which eventually led to the brawl. The most surprising thing was when the arena fights made the event a show of force among students, which when students are won from the brawl, then regarded as a hero.